Análise da recidiva local do câncer de mama em mulheres submetidas à cirurgia conservadora - Tovar, Juliana Rodrigues (2013)
Introduction: Conservative surgery is now considered the procedure of choice when a woman is affected by a tumor at an early stage. As a consequence of conservation of breast tissue, the local recurrence of cancer is a growing concern. Objectives: To describe the sociodemographic and clinical profiles of women with local recurrence of breast cancer, undergoing conservative surgery Santa Rita Hospital in Vitória, Espírito Santo State, Brazil, from January 2000 to December 2010, to examine the association between clinical and sociodemographic and the incidence of local recurrence and analyze local recurrence-free survival of these women. Method: Two studies were performed: the first one is a retrospective cohort study and the second refers to a survival study using secondary data. The sample consisted of 880 women. To estimate the survival period in general and by stratum, the Kaplan Meyer method was employed. The independent effect of variables was checked by Cox/ s model of multivariate proportional risk, while statistical significance was tested through the log-rank method Results: The breast recurrence occurred in 60 patients (6,8%) and the average time between surgery and recurrence of 35,5 months. In multivariate analysis, we identified hazard ratio for the age group up to 39 years (p=0.083 and HR=6.19), positive surgical margin involvement (p = 0.001 and HR = 3.49) and Her-2 positive (p=0.033 and HR=1.89). Conclusions: The selection of each patient to the most appropriate management must be done carefully in order to establish the main sociodemographic and clinical characteristics that might help to choose the best treatment. Similarly, the choice of the best surgical technique is essential to reduce spending on treatments rescue and decrease the psychological suffering of the patient.